Strategi Pemanfaatan Youtube Dalam Bidang Dakwah Oleh Ulama Aceh - Arif Ramdan Sulaeman; Anhar Fazri; Fairus Fairus (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2020)
The development of information technology is very influential in the delivery of information to the public, especially social media youtube which is used to convey the message of da'wah. At this time the development of communication technology has many impacts on humans including changes in behavior, ranging from lifestyles, ways of learning, ways of shopping, and also methods in studying also use models that fit the current era. And so also with the way someone found his God, can be found via the sophistication of communication tools like today. The author in this case studies